PENGAWASAN DINAS KESEHATAN DALAM PENGOPERASIAN DEPOT AIR MINUM ISI ULANG DI KECAMATAN PINOLOSIAN KABUPATEN BOLAANG MONGONDOW SELATAN - PAPUTUNGAN, RIKSAN; RARES, JOYCE JACINTA; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: This research aims to know the supervision of health services in the operation of the depot drinkingwater refill in Bolaang Mongondow Regency South. This study uses qualitative methods with the informantsconsisting of the head of the section of health and environment (KESLING); 2 environmental health staffperson; The owner of the DAM (the Depot drinking water) 5 persons; Employees of 5 people. Data collectiontechniques used are interviews, observation and documentation. Qualitative data were analyzed withdescriptive narrative supported by primary and secondary data. The results showed that (1). Supervision ofthe health services in the operation of the Depot drinking water Refill in district Pinolosian South BolaangMongodow in the know of the results of the study have not been fullest. (2) the examination of the water areroutinely performed Office of South bolaang mongondow Regency health incompatible with permenkes no736 of the Year 2010 about governance oversight of the quality of drinking water.Keywords: Supervision, Operation, DAM (Depot Drinking Water), Bolsel